A relict new species of Oreobates (Anura, Strabomantidae) from the Seasonally Dry Tropical Forests of Minas Gerais, Brazil, and its implication to the biogeography of the genus and that of South American Dry Forests - Teixeira, Mauro; Amaro, Renata Cecília; Recoder, Renato Sousa; de Sena, Marco Aurélio; Rodrigues, Miguel Trefaut (Zootaxa, 2012)
A new species of Oreobates is described from Cavernas do Peruaçu National Park, Januária, Minas Gerais state, in theAtlantic Dry Forests of Brazil. The new species is distinguished from all other Oreobates by having the following combi-nation of characters: large tympanum, discs broadly enlarged and truncate on Fingers III and IV, smooth dorsal skin, nup-tial pads absent, snout subacuminate, and a very short pulsatile (2–3 pulses) single-noted advertisement call with dominantfrequency of about 3150 Hz, and no harmonic structure. Molecular phylogenetic analyses using partial sequences of themitochondrial genes cytochrome b (cyt b) and 16S using multiple outgroups recovered the new species within Oreobatesand sister to O. heterodactylus. The latter species inhabits the Dry Forests of Mato Grosso (Cerrado) and Bolivia (Chiq-uitano forests), and is strictly associated to these habitats, which suggests a preterit connection between Chiquitano andAtlantic Dry Forests. The discovery of a new Oreobates in the Atlantic Dry Forest is of great importance for the conservation of these dry forests, as it is known only from this type of habitat.